Christianity, Islam, and nationalism in Indonesia - Farhadian, Charles E., 1964- (Routledge contemporary Southeast Asia series ;, 2005)
"Christianity, Islam, and Nationalism in Indonesia focuses on Dani Christians of West Papua, providing a social and ethnographic history of the most important indigenous population in the troubled province. It presents a captivating overview of Dani conversion to Christianity, examining the social, religious, and political uses to which they have put their new religion." "Farhadian provides the first major study of a highland Papuan group in an urban context, which distinguishes it from the typical highland Melanesian ethnography. Incorporating cultural and structural approaches, the book affords a fascinating look into the complex relationship among Christianity, Islam, nation making, and indigenous traditions. Based on research over many years, Christianity, Islam, and Nationalism in Indonesia offers an abundance of new material on religious and political events in West Papua. The book underlines the heart of Christian-Muslim rivalries, illuminating the fate of religion in late-modern times."--BOOK JACKET.